PENERAPAN PENDIDIKAN KARAKTER PADA KEGIATAN EKSTRAKURIKULER MELALUI METODE PEMBIASAAN - A. MUSTIKA ABIDIN (Didaktika : Jurnal Kependidikan, 2018)
This research shows the importance of applying character education to extracurricular activities through habituation methods. Extracurricular activities are educational activities outside the subjects to assist the development of students according to their needs, potential, talents, and interests through activities specifically organized by capable educators or education staff who have authority in schools. Therefore, in order to accelerate the implementation of character education as a reflection of the implementation of national education goals, namely by applying character education into the curriculum of educational institutions or extracurricular activities through habituation methods that aim to develop potential, talent, interest, ability, personality, cooperation and independence optimally students who in the end have good character.